Introducing Early Financial Literacy through Saving and Simple Recording Activities for TPA An-Najwa Students in East Jakarta - Imelda Sari; Andri Gunawan; Masagus Asaari (Entrepreneurship and Community Development, 2026)
This Community Service (PKM) activity aimed to improve early childhood financial literacy through the “Happy to Save” (GEMBUNG) and “Happy to Record” (GENCAT) programs for students at the An-Najwa Al-Qur'an Education Park (TPA), Palasan, Cakung, East Jakarta. The program was motivated by the low awareness of elementary school-aged children regarding saving habits and simple financial record-keeping. The activity was implemented through educational sessions, simulations, games, and direct mentoring, using an interactive, practical approach. The program consisted of two main activities: education on the importance of saving and training in simple financial recording using mini savings books. The results showed increased student understanding and awareness of saving behavior, reflected in students' ability to distinguish needs from wants, record daily savings, and begin saving regularly after the program. Participants also demonstrated high enthusiasm and active participation throughout the activities. In addition, the program received positive support from TPA management and parents, indicating its potential for sustainability as part of character-building education. Therefore, the GEMBUNG and GENCAT programs can serve as an initial foundation for developing financial literacy and responsible financial behavior from an early age.